c-Myc-targeted therapy in breast cancer: A review of fundamentals and pharmacological Insights - Stipp, Maria Carolina; Acco, Alexandra (Gene, 2025)
•c-Myc is an oncogene, highly expressed in breast cancer (BC).•c-Myc expression is most prevalent in triple-negative breast cancer (TNBC).•c-Myc is linked to several BC hallmarks, including cell proliferation, differentiation, autophagy, apoptosis, and protein biosynthesis.•Natural and synthetic substances have been studied in in silico, in vitro, and in vivo breast cancer models.•The c-Myc inhibitor OMO-103 is in Phase II clinical trial for advanced cancer patients. The oncoprotein c-Myc is expressed in all breast cancer subtypes, but its expression is higher in triple-negative breast cancer (TNBC) compared to estrogen receptor (ER+), progesterone receptor (PR+), or human epidermal growth factor receptor 2 (HER2+) positive tumors. The c-Myc gene is crucial for tumor progression and therapy resistance, impacting cell proliferation, differentiation, senescence, angiogenesis, immune evasion, metabolism, invasion, autophagy, apoptosis, chromosomal instability, and protein biosynthesis. Targeting c-Myc has emerged as a potential therapeutic strategy for TNBC, a highly aggressive and deadly breast cancer form. This review highlights c-Myc as a pharmacological target, discussing antitumor compounds in preclinical and clinical trials. Notably, the c-Myc inhibitor OMO-103 has shown promise in a Phase II clinical trial for advanced cancer patients. Further research is needed to develop new drugs targeting this gene, protein, or its pathways, and additional studies on cancer patients are encouraged.